The American political tradition and the men who made it - Hofstadter, Richard, 1916-1970 (New York : Vintage Books, 1973)
Reprint of the ed. published by Knopf, New York
Bibliography; p. 463-501
Keywords: United States -- Politics and government; United States -- Biography